Famotidine Repurposing for Novel Corona Virus Disease of 2019: A Systematic Review - Chenchula, Santenna; Ray, Avik; Sadasivam, Balakrishnan (Drug Research, 2021)
Background COVID-19 caused by SARS-CoV-2 was declared as a global pandemic by the WHO. Famotidine is a histamine-2 (H2) receptor antagonist which blocks the H2 receptors in the parietal cells, decreasing gastric acid secretion. Our review aims to study all the available scientific evidence on famotidine research outcomes systematically to introspect its clinical efficacy and probable mechanisms and clinical efficacy against SARS-CoV-2.Methodology An electronic search of PubMed, Scopus and Google Scholar was performed using MeSH terms “SARS CoV-2” OR “COVID-19” AND“FAMOTIDINE”. Relevant informationwas extracted from studies reporting the efficacy of famotidine in COVID-19.Results We found a total of 32 studies, out of which only 14 were relevant and were included in our review.Molecular computational studies showed that famotidine selectively acts on viral replication proteases papain-like protease (PLpro) and 3-chymotrypsin-like protease (3CLpro). Additionally, it acts via inverse-agonism on the H2 receptors present in neutrophils and eosinophils which leads to inhibition of cytokine release. Clinical study findings have pointed toward significant improvements in COVID-19 patient-reported symptoms in non-hospitalized patients and reduction in intubation or death in critically ill patients associated with the usage of famotidine. However,in one of the studies,famotidine has failed to show any significant benefit in reducing mortality due to COVID-19.Conclusion Famotidine has the potential to answer the ongoing global challenge owing to its selective action on viral replication. Additionally, clinical findings in COVID-19 patients support its efficacy to reduce clinical symptoms of COVID-19.We suggest that further optimally powered randomized clinical trials should be carried out to come up with definitive conclusions.
Keywords: Famotidine; Infectious disease; SARS-CoV-2; COVID-19; drug repurposing